Franchising in women’s branded lingerie industry - Eloranta, Mia (fi=Turun yliopisto|en=University of Turku|, 2018)
Fashion and outerwear apparel industries have been of interest for researchers for decades. However, only recently has the interest towards intimate apparel been rising. The industry is constantly growing, which has resulted in the academics starting to pay more attention to the special characteristics related to the market. Lingerie market is a volatile, unpredictable and competitive industry where the conscious and unconscious rationale of the consumer has a significant effect on purchasing behavior. Competitive environment encourages lingerie brands to expand internationally and many of them use franchising in doing so. Consequently, this research contributes to the existing studies on intimate wear focusing on lingerie branding and the use of franchising by exploring the possible advantages of franchising for lingerie brands. This research applied a qualitative research approach. The data was collected by interviewing lingerie professionals, using semi-structured interviews. The primary data was supplemented by using secondary data by collecting and analyzing information found from international lingerie brands’ websites. The theoretical framework of this research is based on previous academic literature, emphasizing the concepts of brand identity and personality, brand equity and brand citizenship behavior. Consequently, it combines the literature on franchising and integrates it in the context of lingerie. The findings of the research support the existing studies on the importance of branding for lingerie retailers. Especially customer loyalty and brand awareness are the most crucial dimensions of brand equity for lingerie brands. The findings prove that franchising can create competitive advantage for lingerie brands by offering their local knowledge of the market and by spreading the brand awareness, hence enhancing the brand equity measures of the lingerie brand. However, the findings suggest that there are situational factors that affect lingerie retailers’ decision to become franchisors, thus showing that franchising is beneficial for lingerie retailers only under certain circumstances. The results demonstrate how franchising is beneficial mainly for big brands aiming to expand internationally. For small, domestically operating brands it does not necessarily create competitive advantage. Based on this research, the importance of branding should be emphasized within the retailers. In addition, the decision to become a franchisor and the benefits it could offer, should be considered carefully within the light of this research.